2020
DOI: 10.4103/jehp.jehp_684_19
|View full text |Cite
|
Sign up to set email alerts
|

Effects of training based on the health belief model on Iranian women's performance about cervical screening: A systematic review and meta-analysis

Abstract: CONTEXT: Pap smear test is one of the most important actions in preventing cervical cancer. This study aimed to perform a meta-analysis on all related literature about the effects of health belief model (HBM)-based training on Pap smear screening test performance of Iranian women. METHODS: The search was performed in Scopus, PubMed, and Web of Science. Eligibility criteria were limited to English and Persian language articles with experimental or semi-experimental metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
17
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 25 publications
6
17
1
1
Order By: Relevance
“…28 Furthermore, the results of a review study based on the HBM are consistent with the findings of the current study. 10 In addition to utilizing lecture techniques, this study promoted Point, are consistent with the findings of the current study. 13 In another study, which was conducted in Iran, three face-to-face training sessions based on the constructs of the Health Belief Model were implemented for 80 rural women, and similar results were reported.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…28 Furthermore, the results of a review study based on the HBM are consistent with the findings of the current study. 10 In addition to utilizing lecture techniques, this study promoted Point, are consistent with the findings of the current study. 13 In another study, which was conducted in Iran, three face-to-face training sessions based on the constructs of the Health Belief Model were implemented for 80 rural women, and similar results were reported.…”
Section: Discussionsupporting
confidence: 88%
“…3 Also, other studies based on HBM showed that educational interventions can be effective in this regard. 10,11 The most important action that led to the change in self-efficacy in the present study, was providing objective patterns through role model individuals who had succeeded in overcoming their fears and doing pap smears, as well as engaging the audience in discussion and using their previous experiences. In addition, some skills to overcome the fears were presented to the participants.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Many studies [ 10 , 11 ] have confirmed that HBM education interventions can improve patients' cognition of disease and improve patients' confidence and compliance with treatment. Previous evidence [ 12 , 13 ] suggests that HBM-based education can improve women's perceived susceptibility to cervical cancer and perceived self-efficacy to participate in cervical cancer screening and increase screening coverage. HBM educational interventions [ 14 ] can help cancer patients fight the disease and survive longer.…”
Section: Introductionmentioning
confidence: 99%